Palm Composite: Composite Products from Palm Ash Waste - Ragunathan, Santiagoo; Johnson, Anbu Clemensis, Dr.; Salmah, Hussiensyah, Dr. Ir.; Azlinda, Abdul Ghani; Che Muhd Ruzaidi, Ghazali, Assoc. Prof.; Roshasmawi, Abdul Wahab (C. I. S. Network, 2010)
Ragunathan Santiagoo and his team won gold for Palm Composite: Composite Products from Palm Ash Waste. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.